STUDI FLORISTIK DI KAWASAN PLASMA NUTIFAH UNTUK MENDUKUNG PENEPATAN PLOT KONSERVASI GENETIK TENGKAWANG (Shorea spp) DI KALIMANTAN BARAT - Jayusman Jayusman (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2011)
A research was done at natural tropical forest in forest concession of PT : Suka Jaya Makmur (SJM).Ketapang. West Kalimantan . The objective of the study is germplasm area in natural Forest. The aims of this floristic study were to investigate the potensial and distribution of tengkawang tree species. Tengkawang kernel is one of the fomous Non –Wood Forest Product (NWFP), it is rescources of on importance vegetable fat. The inventory was conducted using line plot method in each area of 26 Hectares. 130 sample plots were made up systematically within 13 line plot. The sample plot had a square shape with nested sampling area measured 20 mx 20 m for tree stage, 10 m x 10 m for pole stage, 5 m x 5 m for sapling stage and 2 m x 2 m for seeding stage. The result reveal that the germplasm consisted of 75 species were dominated by industralwood species . The germpalsm are was dominated by Shorea leprosula with importance value (31.01%). Eugenia cymosa (26.32%).Litsea Firma (18.11%) and Shorea laevis (16.02%) respectively . Some tengkawang trees were found in the study area with important value were varied were Shorea pinnanga (9.43%) . Shorea macrophylla (4.11%). Shorea macistopterix (0.63%) respectively but the famous of tengkawang tree (Shorea stenoptera)was not found in the study area. Therefore, block 35 & 36 PT SJM germplasm area unrepresentative for tengkawang genetic concervation plat.